Improving The Motivation of Junior High School Students in Learning English Using Graphic Media - Taufik, M. Rama Taufik; Peri Andrian; Haris Pratama; L. Irwan Hadidi; Slamet Riadi Jaelani (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This journal explores the possibility of using graphic media to motivate junior high school students to learn English. Traditional methods of teaching English often fail to arouse interest and enthusiasm in students. Therefore, it is important to seek innovative and engaging ways to facilitate language learning. The purpose of this study was to investigate how incorporating graphic media such as cartoons, illustrations, and visual aids positively impacts student motivation, learning experience, and language skills. Research demonstrates the effectiveness of graphic media in promoting active participation, creativity, and a deeper understanding of English concepts. The results encourage educators to integrate graphic media into classroom practice, paving the way for a more dynamic and enjoyable learning environment.